2023
DOI: 10.2147/jmdh.s403206
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Structured Kangaroo Care Education on Premature Infants’ Weight Gain, Breastfeeding and Length of Hospitalization in Malaysia

Abstract: Purpose Kangaroo care is a complementary humanistic intervention based on a family-centered care model. This study investigated the effects of a locally contextualized, structured kangaroo care education program on weight gain, breastfeeding rate and length of hospitalization for premature infants. Patients and Methods This longitudinal quasi-experimental study with pre- and post-intervention design involved 96 infants born between 28 and 37 weeks of gestation for three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Similar critical roles by family members to enhance KMC was documented in African and Scandinavian studies (23,24). Similar ndings were found in other studies where structured care educational programs for families at NICU have shown bene ts (22).Our results in conjunction with previous results, support the importance of availability of health facilities, and the policy of allowing family members in the NICU for KMC practice. Among the di culties expressed, body pain was reported by approximately 40% of the mothers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar critical roles by family members to enhance KMC was documented in African and Scandinavian studies (23,24). Similar ndings were found in other studies where structured care educational programs for families at NICU have shown bene ts (22).Our results in conjunction with previous results, support the importance of availability of health facilities, and the policy of allowing family members in the NICU for KMC practice. Among the di culties expressed, body pain was reported by approximately 40% of the mothers.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to CMCH, a study conducted within Malaysia demonstrated a shorter hour of cKMC practices within the NICU cohort after discharge (22). We hypothesise that this could be due to the adequate weight gain and stabilisation before discharge and therefore less motivation among the families to practice KMC.…”
Section: Discussionmentioning
confidence: 86%
“…Bene ts of SSC SSC has been shown to have positive effects on both infants and mothers including lowering infant mortality rates, easing the transition to extrauterine [20], promoting thermoregulation and early hemodynamic stability even in premature babies, promoting metabolic balance and optimal neurological development, decreasing the incidence of postpartum depression, reducing infant crying, improving mother and infant bonding [21,22]. One of the most studied bene ts of SSC is its impact on breastfeeding, which is a crucial practice for maternal and child health [23,24]. SSC promotes early breastfeeding and enhances latching, increases the mother's milk production and supply and has been associated with the both longer exclusive breastfeeding times for the rst six months of life and overall longer breastfeeding duration, which includes the interval of time after the rst six months of life.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, Mohamed et al [ 33 ] showed highly significant differences between pre- and post- education for KMC knowledge. Similarly, Samsudin et al [ 34 ] conducted a study in Malaysia and used a modified KMC questionnaire that showed that knowledge levels significantly increased post-intervention, and the post-test knowledge score (M = 46.81, SD = 3.21) taken after the intervention program was significantly higher than the pre-test score. Regarding perceptions of the importance of family participation, Toivonen et al [ 35 ] conducted a study in Finland that showed the highest nursing responses were found for active listening, parents’ trust in nurses, and emotional support.…”
Section: Discussionmentioning
confidence: 99%